Penguatan Literasi Keuangan Syariah Melalui Edukasi Waspada Pinjaman Online dan Judi Ilegal Serta Perencanaan Keuangan Bagi Pelajar di MA Al-Huda Bengkalis - Natasya Humaira; Desy Syamputri; Zul Hendri; Khodijah Ishak (SIGMA : Jurnal Sinergi Mengabdi, 2026)
Sharia financial literacy serves as a fundamental element of Sharia financial management that should be instilled in students from an early age. Developments in the digital era have given rise to various financial issues, notably the increase in cybercrimes—such as predatory online lending and illegal gambling—that threaten the future of the younger generation. Financial literacy levels among students (aged 15–29) remain low, leaving them vulnerable to becoming victims of such cybercrimes. This community service initiative aimed to raise student awareness and understanding regarding the dangers of online lending and illegal gambling, while also enhancing their ability to manage finances effectively. The program employed a participatory-educational approach featuring seminars, interactive discussions, and simulations on creating simple financial plans based on Sharia principles. Participant understanding was evaluated by comparing pre-test and post-test results regarding the risks associated with online lending and illegal gambling, as well as Sharia financial management. The evaluation revealed an 80% improvement in participants' understanding of these issues and Sharia financial management practices. These findings indicate a need for widespread Sharia financial education—particularly among students—to foster wise, responsible financial management aligned with Sharia principles, thereby protecting them from the pitfalls of online lending and illegal gambling.